Measuring The Level of Student Satisfaction with Teacher Performance with Algorithmic Method C4.5 - Nur Apriliana Cahyani; Erza Sofian (International Journal of Education, Information Technology, and Others, 2022)
Satisfaction or dissatisfaction is the conclusion of the interaction between expectations and experiences after using the services or services provided. However, more service satisfaction assessments are done with survey calculations that explain relationships that are difficult to interpretation. Data mining with the C4.5 Algorithm technique can create decision trees that handle discrete type attributes and discrete numeric types, as a result of which the resulting data is easily interpreted and has an acceptable level of accuracy. This study aims to find out and analyze how much student satisfaction levels to teacher performance by using the C4.5 Algorithm method. The data was taken from a sample of SMA Negeri 1 Tanjungpinang students. The results of this study showed that SMA Negeri 1 Tanjungpinang students were satisfied with the services provided with a percentage of student satisfaction rate of 90.4% with tangible (physical evidence) as an influential dimension determining the level of student satisfaction. This research has contributed to enriching problem-solving solutions using the C4.5 Algorithm. It is hoped that the results of this study can be applied to improve teacher performance so that the services provided to students can be better and become a reference to improve student satisfaction.